2017
DOI: 10.1016/j.stemcr.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Glycolysis-Optimized Conditions Enhance Maintenance of Regenerative Integrity in Mouse Spermatogonial Stem Cells during Long-Term Culture

Abstract: SummaryThe application of spermatogonial stem cell (SSC) transplantation for regenerating male fertility requires amplification of SSC number in vitro during which the integrity to re-establish spermatogenesis must be preserved. Conventional conditions supporting proliferation of SSCs from mouse pups have been the basis for developing methodology with adult human cells but are unrefined. We found that the integrity to regenerate spermatogenesis after transplantation declines with advancing time in primary cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
85
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 48 publications
1
85
1
Order By: Relevance
“…Spermatogonial cultures were maintained on mitotically inactivated SIM mouse embryo-derived thioguanine-and ouabain-resistant feeder monolayers (STOs) in mouse serum-free medium (mSFM), devoid of fatty acids and supplemented with the growth factors GDNF (20 ng/mL; Peprotech, NJ, USA) and FGF2 (1 ng/mL; Peprotech). Cultures were kept in glycolysis-optimized conditions in humidified incubators at 37 °C, 10% O2 and 5% CO2 in air (Helsel et al, 2017a). Culture media was replaced every other day, and passaging onto fresh feeders was performed every 6-8 days.…”
Section: Spermatogonial Cultures Id4-egfp Flow Cytometry and Transplmentioning
confidence: 99%
“…Spermatogonial cultures were maintained on mitotically inactivated SIM mouse embryo-derived thioguanine-and ouabain-resistant feeder monolayers (STOs) in mouse serum-free medium (mSFM), devoid of fatty acids and supplemented with the growth factors GDNF (20 ng/mL; Peprotech, NJ, USA) and FGF2 (1 ng/mL; Peprotech). Cultures were kept in glycolysis-optimized conditions in humidified incubators at 37 °C, 10% O2 and 5% CO2 in air (Helsel et al, 2017a). Culture media was replaced every other day, and passaging onto fresh feeders was performed every 6-8 days.…”
Section: Spermatogonial Cultures Id4-egfp Flow Cytometry and Transplmentioning
confidence: 99%
“…Indeed, it was reported that ZIKV is present in the testes of mice in cells that are highly active in cell division including spermatocytes, Sertoli cells and spermatogonia [33]. For survival, spermatogonial stem cells, exhibiting dynamic proliferation, require an environment that favours glycolysis [39]. Why is glycolysis important for proliferation?…”
Section: Astrocytes As a Reservoir For Proliferation Of Infectious Agmentioning
confidence: 99%
“…In terms of the SSC niche, one recent report found that the reduction in O 2 tension during in vitro conditions enhanced the in vivo maintenance of the SSCs' regenerative integrity. SSCs cultured long term in hypoxic conditions (10% O 2 tension rather than the standard 21% O 2 tension), had the capacity to continue spermatogenesis following transplantation in recipient tubules devoid of germ cells [48]. Previous work from the same group had also shown that key glycolysis regulating enzymes were elevated in cultured undifferentiated germ cells [49].…”
Section: Hypoxia Metabolism and The Role Of Inflammationmentioning
confidence: 99%
“…The excess of free fatty acids, however, promotes fatty acid catabolism (i.e. β-oxidation and oxidative phosphorylation) rather than glycolytic activity [48]. Together, there are possible explanations and takeaways from such discrepancies regarding hypoxia and metabolism.…”
Section: Hypoxia Metabolism and The Role Of Inflammationmentioning
confidence: 99%
See 1 more Smart Citation